The Influence of Financial Technology Usage, Lifestyle, Locus of Control, and Parental Income on the Financial Behavior of Students - Agustina, Ayu Fitalina; Kurniawan, Lintang (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This research entitled “The Influence of Financial Technology Usage, Lifestyle, Locus of Control, and Parental Income on the Financial Behavior of Students at the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta” seeks to examine how parental income, lifestyle, locus of control, and financial technology use affect students' financial behavior. The research applied a survey procedure in a quantitative manner through questionnaires distributed to 100 active students. Data were analyzed through validity and reliability tests, F-test, t-test, coefficient of determination, multiple linear regression, and traditional assumption tests using SPSS. The findings indicated that lifestyle, locus of control, and parental income have a positive and significant influence on students' financial behavior, while financial technology usage has a favorable but insignificant impact. These findings contribute to a better understanding of student financial behavior and may serve as a reference for educational institutions and parents in fostering healthy financial habits among students.